Histomorphological Study on the Sweat Glands in Bakerwali Goats - Razvi, Raheeqa; Suri, Shalini; Sarma, Kamal (Indian Journal of Veterinary Anatomy, 2013)
Skin samples from eighteen apparently healthy Bakerwali goats of three different age groups irrespective of the sex were collected for histomorphological studies. Sweat glands were found in clusters. Two types of sweat glands lined by cuboidal epithelium were merocrine and apocrine in nature. The number of sweat glands was found to be more in neonatal age group as compared to young and adults. These glands were found to be maximum at dorsal region of thorax in neonates whereas, at dorsal region of loin in young and adults. The depth of sweat glands increased with advancement of the age. The sweat glands were surrounded by fine reticular fibres. The epithelium of the sweat glands showed positive reaction for PAS and bound lipids.